Nanostructured mullite steam oxidation resistant coatings for silicon carbide deposited via atomic layer deposition. Issue 6 (15th January 2018) - Hoskins, Amanda L.; Coffey, Aidan H.; Musgrave, Charles B.; Weimer, Alan W.
Abstract: Oxidation resistant, thin, pinhole‐free, crystalline mullite coatings were deposited on zirconia and silicon carbide particles using atomic layer deposition (ALD). The composition of the films was confirmed with inductively coupled plasma optical emission spectroscopy (ICP OES), and the conformality and elemental dispersion of the films were characterized with transmission electron microscopy (TEM) and energy dispersive X‐ray spectroscopy (EDS), respectively. The films are deposited on the particle surface with a deposition rate of 1 Å/cycle. The elemental concentration of aluminum relative to silicon in the film was determined to be 2.68:1 which agrees closely with the ratio of stable 3:2 mullite (2.88:1). A high‐temperature anneal for 5 hours at 1500°C was used to crystallize the films into the mullite phase. This work represents the first deposition of mullite films by ALD. The mullite and alumina‐coated particles were exposed to high‐temperature steam for 20 hours at 1000°C to assess the oxidation resistance of the films, which reduced the oxidation of silicon carbide by up to 62% relative to uncoated particles under these conditions. The activation energy of oxygen diffusion in the films was determined with density functional theory, and the computational results aligned well with the experimental outcomes.